PENINGKATAN SKILL DAN DIGITAL MARKETING INDUSTRI MAKANAN PADA USAHA MIKRO â€œCAHAYAâ€ PASURUAN - Sri Utami Ady; Alvy Mulyaningtyas; Litafira Syahadiyanti; Fany Meyranda Putri; Mar'atus Sholikhah; Duvan Hermansyah Yudi Astono (Universitas Mataram, 2023)
The home industry is a household craft business with 1-4 workers. The home industry that was a partner in this PKM was the